CORRELATION OF GENDER AND LEPTIN WITH ANALGESIC EFFECT OF TRAMADOL IN RATS - Satyam, Shakta Mani; Bairy, Laxminarayana Kurady; Devi, Vasudha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of the study was to investigate the correlation of gender and serum leptin level with analgesic modulation of tramadol in Wistar rats. Methods: A total of 48 Wistar rats (body weight 100â€“150 g), 24 each male and female Wistar rats were randomly divided into two groups (n=6/group) (Group I - Control- 0.9% NaCl; 1 ml/kg/day i.p. and Group II - Tramadol 10 mg/kg/day i.p.) for each nociception model - plantar test and acetic acid induced writhing test. The treatment duration was of 5 days. Paw withdrawal latency (PWL) was assessed using plantar test and writhing movements were observed following administration of 0.8% acetic acid; 10 ml/kg i.p. Results: PWL was significantly decreased (p<0.001) and both number of writhing movements and serum leptin concentrations were significantly increased (p<0.001) in female control group compared to male control group. In tramadol treated female rats, PWL was significantly decreased (p=0.005) and both number of writhing movements and serum leptin concentrations were significantly increased (p<0.001) in comparison with the tramadol treated male rats. PWL was negatively correlated with serum leptin concentration (Pearson correlation coefficient= âˆ’0.826, two-tailed significance= 0.000), and writhing movements were positively correlated with serum leptin concentration (Pearson correlation coefficient= 0.505, two-tailed significance= 0.012). Conclusions: The present study revealed that female rats have more serum leptin concentration than male rats which could be one of the possible reasons for having more pain sensitivity to noxious stimuli in female rats compared to male rats. Tramadol treatment at the dose of 10 mg/kg for 5 days has decreased serum leptin level in rats which might be one of the additional mechanisms of tramadol to reduce pain.